2020
DOI: 10.1186/s12882-020-01821-w
|View full text |Cite
|
Sign up to set email alerts
|

Association between extracellular volume control and survival in patients on short daily haemodialysis

Abstract: Background: Fluid overload (FO) assessed by bioimpedance spectroscopy (BIS) is associated with higher mortality risk in maintenance haemodialysis (HD). The aim was to assess if a better management of FO through short daily haemodialysis (SDHD) could improve survival. Methods: Retrospective analysis of patients who were on HD 3 sessions/week for at least 3 months and shifted to in-centre SDHD (5 or 6 sessions/week, 2 to 3 h/session) between July 2012 and June 2016 at 23 dialysis units in Brazil. The 12-month ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Indeed, the long-term exposition to excessive extracellular volume is a much stronger predictor of death risk than the presence of FO at admission on HD, as shown by Zoccali et al [ 8 ]. We demonstrated in a previous study that even prevalent patients with FO while on conventional HD, after switching to short daily HD and subsequent correction of FO, had the same survival rate as those patients on short daily HD who were not with FO when they were still on conventional HD [ 20 ]. This finding corroborates once again that FO would be a modifiable risk factor and that its correction should be considered a priority in the clinical management.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the long-term exposition to excessive extracellular volume is a much stronger predictor of death risk than the presence of FO at admission on HD, as shown by Zoccali et al [ 8 ]. We demonstrated in a previous study that even prevalent patients with FO while on conventional HD, after switching to short daily HD and subsequent correction of FO, had the same survival rate as those patients on short daily HD who were not with FO when they were still on conventional HD [ 20 ]. This finding corroborates once again that FO would be a modifiable risk factor and that its correction should be considered a priority in the clinical management.…”
Section: Discussionmentioning
confidence: 99%
“…This criterion enabled us to include as many eligible participates as possible, and guaranteed that they are all MHD patients as well. Usually, being on HD treatment more than 3 months is recognized as MHD patients, and most studies in HD population enrolled participants on HD more than 3 months [ 38 40 ]. Furthermore, some research suggested that 3 months might be long enough to make a difference on the progression of LVH in HD population [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also causes serious complications; some of the highlighted recurrent clinical conditions as intra-dialytic hypotension, intra-dialytic hypertension, Hyperkalemia, edema and organ failure during dialysis sessions. Uncontrollable high blood pressure and edema are the main risk factor developing heart disease (7) . The prevalence of hypertension during dialysis is 15% to 50% of patients receiving hemodialysis treatment (8) .…”
Section: Introducationmentioning
confidence: 99%